Analisa Pengaruh Konsentrasi Limbah Serat Aren dan Limbah Kertas dalam Pembuatan Papan Komposit terhadap Modulus Rupture - Khayati, Miftahul; Indarto, Muklis; Wardana, Fandi Wijaya Kusuma; Widayatno, Tri (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
Composite is a new type of engineered material consisting of two or more materials in which the properties of each material differ from one another both chemical and physical properties and remain separate in the final result of the material. Composites have the characteristics of being lightweight, strong, not easy to corrode, and able to compete with metals. The addition of filler to the matrix aims to strengthen the composite board. Currently, the sugar palm industry in Klaten is growing rapidly and produces solid waste in the form of palm fiber. Besides paper production has increased to reach 13 million tons, the high demand for paper can cause more paper waste produced. In this study, the fillers used are natural fibers from palm waste and paper waste combined in polyester resin to produce good mechanical strength. The variation in this study is the difference in concentration in the palm fiber filler and paper. Comparison of palm fiber and paper as follows: 1,5 g:20 g), (2 g:15 g), (2,5 g:10 g), dan (3 g:5 g). In the fracture constancy test or modulus rupture (MOR), the results obtained in variation A showed results of 178,64 kgf/cm3, variation B of 159,6 kgf/cm3, variation of C was 131,32 kgf/cm3, and variation D is 80,92 kgf/cm3. Variation A shows the best value that is 178,64 kgf/cm3, the results are in accordance with SNI composite board No. 03-2105-2006.